2005
DOI: 10.1016/j.bbmt.2005.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Serious Infections after Unrelated Donor Transplantation in 136 Children: Impact of Stem Cell Source

Abstract: How the infection risks compare after umbilical cord blood (UCB) and bone marrow (BM) transplantation is not known. Therefore, we compared serious infections in the 2 years after pediatric myeloablative unrelated donor transplantation with unmanipulated BM (n = 52), T cell-depleted (TCD) BM (n = 24), or UCB (n = 60) for the treatment of hematologic malignancy. Overall, the cumulative incidence of 1 or more serious infections was comparable between groups (BM, 81%; TCD, 83%; UCB, 90%; P = .12). Furthermore, by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
101
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(103 citation statements)
references
References 22 publications
2
101
0
Order By: Relevance
“…A drawback of UCBT is the delay in reconstitution of T-cell immunity, which increases opportunistic infections. [34][35][36] Treatment of Adenovirus, BK virus, and CMV is challenging, and many UCBT recipients have complications from all 3 viruses. Prior work suggested that recovery of protective T-cell immunity to CMV after UCBT depended on de novo thymopoiesis, which is typically measurable after day 100.…”
Section: Discussionmentioning
confidence: 99%
“…A drawback of UCBT is the delay in reconstitution of T-cell immunity, which increases opportunistic infections. [34][35][36] Treatment of Adenovirus, BK virus, and CMV is challenging, and many UCBT recipients have complications from all 3 viruses. Prior work suggested that recovery of protective T-cell immunity to CMV after UCBT depended on de novo thymopoiesis, which is typically measurable after day 100.…”
Section: Discussionmentioning
confidence: 99%
“…First, recipients of UCBT are at increased risk of viral infections due to lack of adoptive transfer of donor immunity. [19][20][21] The additional course of immunosuppression prior to second UCBT might have further promoted viral reactivation in our patients. Finally most patients required treatment for chronic GVHD, which could have also contributed to the risk of infection.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] These observations indicate that cord blood-derived immune cells have unique immune properties that allow for allogeneic tolerance while preserving the GVL effect.…”
Section: Introductionmentioning
confidence: 99%